2014
DOI: 10.3389/fpsyg.2014.00664
|View full text |Cite
|
Sign up to set email alerts
|

Preparing learners with partly incorrect intuitive prior knowledge for learning

Abstract: Learners sometimes have incoherent and fragmented intuitive prior knowledge that is (partly) “incompatible” with the to-be-learned contents. Such knowledge in pieces can cause conceptual disorientation and cognitive overload while learning. We hypothesized that a pre-training intervention providing a generalized schema as a structuring framework for such knowledge in pieces would support (re)organizing-processes of prior knowledge and thus reduce unnecessary cognitive load during subsequent learning. Fifty-six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 79 publications
(112 reference statements)
1
4
0
Order By: Relevance
“…Identifying whether a well-structured mathematical task is correct or not is more straightforward. Particularly, it is not trivial for pre-service teachers because learners often hold fragmented, partly misconceptual knowledge about learning strategies as already mentioned (Glogger-Frey et al, 2018;Ohst et al, 2014). Roelle and Berthold (2016) found comparable effects as the present ones using contrasting cases holding a very high number of possible comparisons.…”
Section: Limitations and Potential Boundary Conditionssupporting
confidence: 70%
See 1 more Smart Citation
“…Identifying whether a well-structured mathematical task is correct or not is more straightforward. Particularly, it is not trivial for pre-service teachers because learners often hold fragmented, partly misconceptual knowledge about learning strategies as already mentioned (Glogger-Frey et al, 2018;Ohst et al, 2014). Roelle and Berthold (2016) found comparable effects as the present ones using contrasting cases holding a very high number of possible comparisons.…”
Section: Limitations and Potential Boundary Conditionssupporting
confidence: 70%
“…These theories assume certain kinds of (suboptimal) prior knowledge that are difficult to address in learning. Pre-service teachers often show such knowledge (about learning strategies: Glogger-Frey et al, 2018;Ohst et al, 2014;about learning: Vosniadou et al, 2020;Eitel et al, 2021). In line with these theoretical approaches, holding on to such kind of knowledge impeded our participants' learning to some extent.…”
Section: Thinking Processesmentioning
confidence: 88%
“…The question is whether prior knowledge is helpful in ill-structured domains. Ohst et al ( 2014 ) showed that unsystematic prior knowledge needs to be systematized before the actual learning process can successfully take place. Since prior knowledge on ill-structured, complex topics might be unsystematic and—especially in public discussions on bioethical dilemmas—intuitive, prior knowledge might not be as helpful for learning with complex topics as it is in topics from only one domain.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, misconceptions appear to be quite persistent across time (Taylor & Kowalski, 2014). However, research shows that misconceptions can be effectively reduced in the short term when providing refutation texts (e.g., Ferrero et al, 2020;van Loon et al, 2015), refutation lectures (Kowalski & Taylor, 2009;Taylor & Kowalski, 2014), and/or support for conceptually restructuring incorrect knowledge (Ohst et al, 2014). With these interventions, people typically uncover prior conceptions as inaccurate and provide correct information with an explanation.…”
Section: Addressing Teachers' Misconceptions About Self-regulated Learningmentioning
confidence: 99%